Zagadki i agon mędrców w „Królu Edypie” Sofoklesa - Cieśluk, Małgorzata (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The topic of the study entitled Riddles and the dual of sages in Sophocles Oedipus the King is a riddle and its possible meanings, as well as its importance for the interpretation of this tragedy. In the frst part of this study both the prologue and fnal parts of the tragedy are examined as the elements of formal and material opposition. In the second part the confrontation between Oedipus and Teiresias is considered as a traditional dual of sages.

In my study I focus on a problem of possible meanings of the riddles in Sophocles’ Oedipus the King and its importance for the interpretation of this tragedy. Although this problem has already been examined in some other studies, it seems possible to make some new insights about it, when we simultaneously look at both the prologue and fnal parts of the tragedy (kommos and exodos) us the elements of formal and material opposition. Then the conclusions form the basis to examine the function and meaning of confrontation between Oedipus and Teiresias, as well as the riddles in Sophocles’ story about King Oedipus. The comparison of the prologue and the fnal parts of the tragedy reveals “the rule of reversal”, which is important for our understanding of portrait of the hero and his relationships with other characters. During a theatre performance this effect has been clearly created, when the actor who played the role of Oedipus changed his mask. The symbolic image of the mask focused some oppositions, which connect with the kind of passion, activity and passivity of the hero, the hero’s relationship with the gods (especially with Apollo), the limits of human understanding and so on. Thanks to these oppositions as well as the strategy of the points of view in the prologue of the tragedy, we can notice a new perspective to examine the confrontation between Oedipus and Teiresias as a traditional dual of sages. The factor that enables us to judge the competence of the rivals is the skill of solving riddles. As the result of this confrontation, Sophocles, it seems, undermines the competence of the sage in the case of Oedipus, and emphasizes his fault connected with his self-assessment and unentitled participation in the dual of sages.
Oedipus the King by Sophocles riddles and dual of sages
Keywords: Oedipus the King; Riddle; Dual of sages